Cytotoxic response of 5-fluorouracil-resistant cells to gene- and cell-directed enzyme/prodrug treatment - Durinikova, Erika; Plava, Jana; Tyciakova, Silvia; Skvara, Pavel; Vojs Stanova, Andrea; Kozovska, Zuzana; Kucerova, Lucia; Matuskova, Miroslava (Cancer gene therapy, 2018)
Gene-directed enzyme/prodrug therapy (GDEPT) mediated by mesenchymal stromal cells (MSC) was already approved for clinical study on a progressive disease refractory to standard therapy. In this work, we examined the effect of several GDEPT approaches on chemoresistant cells. First, we derived 5-fluorouracil (5-FU)-resistant variant of human colorectal adenocarcinoma cells HT-29 designated HT-29/EGFP/FUR. Our data show that the upregulation of thymidylate synthase (TS) and downregulation of thymidine phosphorylase (TP), orotate phosphoribosyl transferase (OPRT) and dihydropyrimidine dehydrogenase (DPD) contributed to the 5-FU resistance in cancer cells. Next, we combined the MSC expressing either yeast cytosine deaminase (CD-MSC) or fusion yeast CD::uracil phosphoribosyl transferase (CD::UPRT-MSC) and prodrug 5-fluorocytosine (5-FC) in a cell-mediated GDEPT approach. Bystander cytotoxic effect in the direct co-cultures of the tumor and therapeutic cells mixed in a 5:1 ratio resulted in 55% and 70% inhibition of proliferation, respectively. However, the acquired chemoresistance to 5-FU can be overcome by introducing the prodrug-converting transgene into the tumor cells. When the transgene CD::UPRT was expressed in the chemoresistant cells (CD::UPRT-FUR), substantial suicide effect and a 90% decrease in viability was observed using non-toxic concentration of 62.5 µg/ml 5-FC. In summary, we demonstrate here that the transgene introduction circumvented 5-FU resistance in the tumor cells.
Keywords: prekurzory léčiv; Fluorouracil; Mice; nádorové buněčné linie; genetická terapie; myši SCID; Genetic Therapy; Prodrugs; Animals; Cell Line, Tumor; Humans; Mice, SCID; lidé; fluoruracil; zvířata; myši